A novel exploration of irritability in adolescent males: A preliminary study. (June 2023) - Bell, Erica; Pooley, Amanda; Tam, Philip; Boyce, Philip; Bryant, Richard; Porter, Richard; Malhi, Gin S.
Objective: Irritability is a key symptom of mood disorders and is common in adolescence; nevertheless, it is poorly understood and assessed. Research examining irritability and its relationship to mood and anxiety disorders risk factors in adolescent males is lacking. Therefore, the current study aimed to address this gap. Method: An online survey designed to interrogate the relationship between irritability and other risk factor variables was administered to 627 adolescent males (ages 12–17). Findings were analysed statistically using MANOVAs. Results: When divided into high and low irritability groups, higher irritability scores were significantly correlated with higher scores on all risk factor variables. Further, higher irritability scores were associated with higher scores on all variables that indicate an increased risk for development of psychological disorders, such as depression and anxiety. Conclusion: This study is the first to focus on subjective irritability. In adolescent males, it identifies a potentially novel model of irritability's involvement in maladaptive processes relating to emotional dysregulation, behavioural difficulties and anxiety.